Exploring the COVID-19 pandemic’s influence on eating disorders: insights from an Italian residential center - Monaco, Francesco; Vignapiano, Annarita; Meneguzzo, Paolo; Palermo, Stefania; Caputo, Annaluce; Forte, Ilona; Boccia, Antonella; Longobardi, Anna; Di Pierro, Marilena; Panarello, Ernesta; Di Gruttola, Benedetta; Mainardi, Annarita; et al. (Frontiers in Psychology, 2025)
IntroductionThe COVID-19 pandemic has significantly impacted global mental health, exacerbating the prevalence and severity of Eating Disorders (EDs). This study evaluates changes in the presentation and severity of EDs before and after the pandemic at the Regional Residential Center “Mariconda” in Salerno.MethodsThis retrospective cohort study analyzed records from 162 patients admitted to the center between December 2018 and December 2023. The onset of pandemic restrictions in mid-2020 divided the subjects into pre-COVID and COVID groups. Data collected included age, gender, education level, previous hospital admissions, admission diagnoses, body mass index (BMI), and comorbidity with other psychiatric conditions.ResultsAmong the 162 subjects, 115 (71%) were admitted during the pandemic period. This group was significantly younger (mean age: 18.3 vs. 20.6 years, p = 0.009), had lower educational attainment (67% vs. 49% below secondary school diploma, p = 0.025), had a higher rate of prior hospitalizations (49% vs. 26%, p = 0.007), and demonstrated a higher prevalence of severe comorbidities with other mental illnesses (94% vs. 82%, p = 0.009) compared to the pre-COVID cohort. No significant differences were observed in gender distribution, initial diagnoses upon admission, or average length of hospital stay.ConclusionThe findings indicate that the COVID-19 pandemic intensified the presentation and severity of EDs, particularly among younger individuals with lower educational backgrounds. This underscores the urgent need for targeted, integrated treatment approaches for EDs in the context of global crises, including the development of strategies to address the increased severity of comorbid conditions and higher frequency of hospital readmissions observed in this study. These results highlight the necessity of reinforcing multidisciplinary care models that integrate medical, psychological, and social support to address the heightened complexity of post-pandemic ED cases and ensure more effective, long-term treatment outcomes. Future research is essential to explore the long-term effects of the pandemic on EDs, as well as to refine treatment strategies that better support those affected.